Rheological characterization of potassium carbonate deep eutectic solvent (DES) based drilling mud - Rasool, M.H. (Springer Science and Business Media Deutschland GmbH, 2021)
Different additives are added in the drilling mud to increase its efficiency in terms of its rheology and filtration properties. Recently, the application of ionic liquids (ILs) has been exploited by various investigators as a drilling additive for improving the mud rheology. The more recent studies have shown that imidazolium-based ionic liquids (the most used class of ionic liquids in drilling fluids) are toxic. Moreover, the advancement in green chemistry has put a big question mark on the greener nature of ionic liquids because they are non-biodegradable and generally very expensive. Deep eutectic solvents (DES) are the non-toxic and cheaper alternative of ionic liquids possessing the same qualities as of ILs. In our previous work, we used potassium carbonate and glycerol-based DES as a drilling fluid additive. We found that DES has successfully improved the mud rheology and filtration properties of the mud. In this current study, various characterizations have been conducted to understand the underlying mechanism behind DES as a rheology modifier. The characterization shows the improvement in rheology is due to the intercalation of DES between alumino-silicate layers and interaction of DES with clay which alters edge to face orientation of sodium bentonite and ultimately its dispersion behaviour. The addition of DES decreases average grain size and disperses the clay particles in mud slurry which reduce the overall permeability and porosity of the filter cake thus improving the filtration behaviour of the mud. Moreover, the behaviour of DES based mud is modelled at 25Â Â°C and 100Â Â°C which shows DES-based mud follows HerschelâBuckley model and exhibits shear thinning behaviour even at elevated temperature. Â© 2021, The Author(s).